An improved CPHD filter for unknown clutter backgrounds - Mahler, R.; Vo, Ba Tuong (S P I E - International Society for Optical Engineering, 2014)
The “clutter-agnostic” CPHD filter was introduced at the 2010 SPIE Defense, Security and Sensing Symposium in 2010, and has been investigated in subsequent papers. This “k-CPHD filter” was capable of multitarget detection and tracking in unknown, dynamically changing clutter backgrounds. It was also capable of estimating the entire intensity function of the clutter process. The purpose of this paper is to introduce a generalization of this filter. The generalized k-CPHD filter has the following two major improvements: (1) a formula for the probability distribution on the number of targets (target cardinality distribution); and (2) a formula for the probability distribution of the number of clutter measurements (clutter cardinality distribution). More generally, the entire probability distribution of the clutter process can be estimated.